BERBELANJA ONLINE SEBAGAI PILIHAN BAGI PEREMPUAN DI NUSA DUA - Sharon Khatlean, Bawiling Mawar; Kebayantini, Ni Luh Nyoman; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT This study aims to understand and explain the development of online shopping with the emergence of online stores or online shop as an option to shop for women in the village of Bualu, Banjar Bualu-Nusa Dua. This study applied a qualitative approach by using in-depth interview and using network society theory from Manuel Castells as an analytical tool. The result shows that work routines, long distance to reach shopping place and traffic congestion and the development of information network with the convenience offered globally provide encouragement for women in Bualu Village to choose online shopping as a consideration in shopping. The behavior of women in Bualu Village using their capital for online shopping reflects the submission of information that has implication for the formation of an informational society that has a tendency to meet the needs of life effectively and efficiently. Referring to the urgency of research finding, further research is strongly recommended to find out other factors that drive online shopping behavior. Keywords :Change, Need, Woman, Online